The Formula of Jelly Drink Banana Fruit (Musa paradisiaca Typical) and Soybeans (Glycine max L. MERR) for Obesity - Elia Wardatul Fitri; Budi Setiawan; Ikeu Ekayanti (Jurnal Penelitian Pendidikan IPA, 2024)
The diversity of food and beverage products is very important, especially for the needs of weight loss for obesesity. Therefore, the development of functional food sourced from local raw materials is needed. Therefore, the aim of this research is to find a jelly drink product formula made from bananas and soybeans for obesity sufferers. This research was a completely randomized design (CRD). Organoleptic tests on color, taste, aroma and texture parameters of three Jelly drink formula. The analysis of chemical and physical properties is obtained from the laboratory, and is followed by a test of satiety and desire to eat (desire to eat). Data analysis used descriptive statistical analysis and continued with Anova analysis. The results of this research found that the jelly drink formula (A) had the highest score of the jelly drink formula  (B) and (C. The average test value of  jelly drink formula  (A) is higher than jelly drink formula  (B) and (C). However, the chemical and physical properties tests between formula (A) and (B) and (C) have significant differences. Furthermore, formula (A) contains 24.27% ripe banana and soybeans, 1.45% carrageenan, 0.48% citric acid, and 0.97% tropicana slim sugar from a total of 206 grams of ingredients. Jelly drinks have the highest organoleptic value and nutritional content for suitable for  obesesity. The results of the satiety test showed that 46.66 respondents felt full for 2.5 hours, and only 20 respondents felt full for 1.5 hours after consuming jelly drink products. Therefore, formula (A) can be as a functional food for obesity.